PEMBUATAN SEDIAAN BALSEM STICK DARI SEREH (Cymbopogon citratus (DC.) Stapf) SEBAGAI AROMATERAPI - okto purba (Jurnal Penelitian Farmasi & Herbal, 2020)
Introduction: Lemongrass plants contain essential oils that can be used as aromatherapy. In the context of efforts to improve public health services in Indonesia, traditional medicine has the opportunity as one of the potential alternative treatments. Society uses traditional medicine in the form of herbal medicine, stew, juice or by rubbing directly on the affected part. Method: Sample in this study was African leaves and palm leaveswhich were taken purposively without comparing samples from other regions, To get the essential oil of lemongrass done by distillation. Result: Aromatherapy balm from essential oil is formulated with some concentrations of 0%, 15%, 20% and 25% of the evaluation of balm which has been done to 3 qualified balm formulas and has good physical quality. Concludes: Citronella essential oil can be made into a supply of balm stick with various concentrations, namely 15%, 20% and 25%. Stick balm made from essential oils of lemongrass can give an aromatherapy effect which is characterized by a refreshing aroma when inhaling the balm preparations and can provide a warm sensation. The best concentration as an aromatherapy stick balm preparation is 25% because it gives the highest aroma and test preferences.